Variación multitemporal de la línea de costa de la Bahía San Lucas, Baja California Sur, México y sus ambientes de playas: Multi-temporal variation of the coastline of San Lucas bay, Baja California Sur, Mexico and its beach environments - Núñez, Luis R.; Matiano , Alejandro G.; Núñez, Sandra J. (Boletín del Centro de Investigaciones Biológicas, 2022)
Multitemporal variation in the coastline of San Lucas Bay, Baja California Sur, Mexico and its beach environments was determined. The analysis had a temporality of twenty years (at intervals of ten years: 2000, 2010 and 2020), three high-resolution LANDSAT 4-5 and 8 satellite images were used and the MNDWI was applied. The extraction of the coastline was carried out by vectoring directly on the pixels that are between the wet and dry limits of the beach and for the statistical analyzes the method proposed by the United States Geological Survey (USGS) was used. Of the 61 orthogonal transects, 55 resulted in an erosive state (90.16%) and 6 in accretion (9.84%). The final point rate (EPR) showed a mean shoreline retreat of (-) 1.2 m/yr and the net shoreline movement (NSM) revealed the largest negative distance to be (-) 122.94 m. reflecting marked erosion at the southwestern tip of the bay while accretion was 24.61 m. A relative decline was also seen in 6 of the 7 beach areas. The erosive trend of the San Lucas Bay coastline represents a loss of the beach coastal resource. These indicators serve as a reference for monitoring, planning and management in coastal management policies.